Factors influencing the implementation of organized physical activity and fruit and vegetable snacks in the HOP’N After-School Obesity Prevention Program - Hastmann, Tanis J.; Bopp, Melissa; Fallon, Elizabeth A.; Rosenkranz, Richard R.; Dzewaltowski, David A. (My University, 2013)
Objective: To identify barriers and facilitators for improving the after-school organized physical activity (PA) and snack quality. Methods: After-school staff (Year 1, n = 20; Year 2, n = 17) participated in qualitative, semistructured interviews about the implementation of an after-school obesity prevention intervention. Interviews were recorded, transcribed, coded for common themes, and analyzed using NVivo software. Results: Several factors influencing implementation of PA and fruit and vegetable (FV) consumption were revealed. Facilitators for PA included: staff training, equipment/gym space, and scheduling organized PA. Physical activity barriers included prioritizing PA and lack of school administration support. Fruit and vegetable facilitators included requesting healthier snacks. Fruit and vegetable barriers included cost and low priority of snack. Conclusions and Implications: The success of improving after-school PA and FV snack quality is dependent on many factors, including several organizational system and staff variables. Future research should focus on systemic changes in the after-school environment to increase the priority of daily PA and a healthy snack.
Keywords: Qualitative; Physical activity; Nutrition; Children; After-school; Obesity prevention